PENGARUH MEDIA VIDIO ANIMASI TERHADAP PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN STUNTING DI DESA PENYENGAT OLAK - Nasution, Atika Fadhilah Danaz; Kusmaryati, Pauline; Sengngeng, Ambo (NHM PRESS, 2023)
Indonesia is included in the third country with the highest prevalence in the Southeast Asia / South East Asia Regional (SEAR) region with an average prevalence of stunting under five in Indonesia in 2005-2017 of 36.4%2. Based on basic health research data in 2018, the prevalence of stunting in Indonesia was 30.8%, consisting of very stunting at 11.5% and stunting at 19.3%. Even though it has decreased from 2013 (37.2%), the prevalence of stunted toddlers in Indonesia is still quite high from the threshold set by WHO, namely 20%3, therefore it is necessary to prevent stunting from occurring during pregnancy by increasing knowledge through interesting media. for pregnant women. The increasing development of information and technology now allows video media to increase knowledge. Video is an audio-visual media that can reveal objects and events as they really are so that the information conveyed through the video can be fully understood. The aim of this research is to analyze the influence of animated video media and digital pocket books on pregnant women's knowledge about stunting prevention in Penyengat Olak Village, Muaro Jambi Regency. The design of this research is quasi experimental with a pre test and post test with control group design. The first group used animated video media, while the second group was given a digital pocket book. The results of the research show that there is an influence of animated video media on pregnant women's knowledge about stunting prevention in Penyengat Olak Village, Muaro Jambi Regency with a value of p = 0.000.